Distribution and classification of springs in Bansbari area of Melamchi Municipality, Sindhupalchowk, Nepal (Journal of Nepal Geological Society, 2019)
Springs are the primary source of drinking water and irrigation in hills and mountains in Nepal. In recent years, the life sustaining springs are reported to be drying and degrading in quality. However, there is a lack of information and knowledge in various aspects of springs in Nepal. This has limited the scope for groundwater development and management in hills and mountains. The present study focuses on identifying, surveying and keeping records of spring sources in the Bansbari area of Melamchi Municipality, Sindhupalchowk, Nepal, and intends to understand the distribution of springs in the area. Assessment of spring water quality and classification of springs is other major component of this study. Out of forty-one springs observed in the area, 85% are perennial and others are seasonal in nature. It is found that majority of the springs are located in the middle altitude ranging from 1000 to 1350m above mean sea level and in moderate slope varying from 10° to 35°. In terms of land use, 37% are located in forest followed by 34%in bushes and 29% in agricultural land. In terms of stream density, 61% of springs are located in places with low stream density. In terms of type of deposit, 51% are located in colluviums, followed by 25% in rock and 24% in residual soil. The springs in the study area are classified as depression spring and fracture spring. They are mostly non-thermal with weakly mineralized water ranging from soft to hard. The general order of dominance of major cations in the sampled springs is Ca2+>Mg2+>Na+>K+ and major anions is HCO3-> Cl->SO42-. Springs of magnitude fifth and less are observed in the study area with significant decrease of discharge in the dry season. Regular monitoring of spring discharges is recommended to quantify the groundwater in the area.